Les « devoirs » : une pratique sociale à la croisée des espaces éducatifs ? - Rémi Bonasio; Philippe Veyrunes (Recherches en Éducation)
French research on homework are quiet recent. They complete the Anglo-Saxon literature on that topic which essentially considered homework in their statistical relationship to academic achievement. We draw up a synthesis of the most recent works to understand this subject’s social construction. We focus on the links between work inside and outside the classroom gathering teachers, pupils, families and extracurricular leaders. These research point out several difficulties generated by this practice, learning inequality’s construction in particular. Studying this practice requires to deal with different educational spaces crossed by issues sometimes convergent and often divergent: a complexity we may consider.